Hubungan Antara Beban Kerja Work From Home, Status Ekonomi, Lingkungan Kerja dengan Tingkat Stres Selama Masa Pandemi Covid-19 pada Pegawai Negeri Dinas Kesehatan Kota Baubau - Sri Erna Mardiyanti; Taswin Taswin; Waode Azfari Azis; La Ode Muh Taufiq (Kampurui Jurnal Kesehatan Masyarakat, 2022)
Covid-19 has become a global pandemic that infects humans all over the world. The purpose of this study is to determine the relationship between variables, namely the independent variable and the dependent variable. The independent variables are the workload of work from home, economic status, work environment, and the dependent variable is the level of stress during the Covid-19 pandemic for civil servants at the Baubau City Health Office. This type of research is quantitative with a cross sectional design, the population is 75 civil servants, the sample is drawn using the total sampling technique, the research time is carried out in February-March 2021. The data collection is through primary data, namely questionnaires and secondary data. Data analysis using univariate analysis and bivariate analysis, using chi-square test by reviewing the p-value test if < alpha (α = 0.05) then it is said to be meaningful. The results of the statistical test showed that the variables related to stress levels during the Covid-19 pandemic were the work from home workload variable (p=0.044<α=0.05), the economic status variable (p=0.048<α=0.05), and the work environment (p=0.033<α=0.05). The conclusion of the study is that there is a relationship between the workload of work from home, economic status, work environment and stress levels during the Covid-19 pandemic in civil servants of the Baubau City Health Office. It is hoped that the Baubau City Health Office will continue to pay attention to the welfare of employees who continue to work during the current Covid-19 pandemic and can accept the obstacles/difficulties of tasks experienced by employees by opening consultation services during routine meetings as a means of channeling anxiety experienced by employees.